School-wide positive behaviour support the Australian handbook - Barker, Katrina; Poed, Shiralee; Whitefield, Phillip (Abingdon, Oxon Routledge, Taylor & Francis Group, 2023)
"Drawing upon twenty years of experience putting the Positive Behaviour Support framework into practice, this is the first definitive handbook to document the ways in which Australian schools have embraced and applied school-wide Positive Behaviour Support, and to provide guidance on implementation. Written by key Australian researchers and implementers with extensive expertise, School-Wide Positive Behaviour Support: The Australian Handbook is an important contribution to the work of school leaders and teachers. This book illustrates the significant contribution of PBS to improving schools and the potential for its systems approach to be expanded across education systems. The book's structure corresponds to the theme of a continuum of supports, addressing the key conceptual foundations of PBS, and its representation within school-wide implementation. Each chapter comprises a mix of research, practical case studies and examples, and features learning intentions, keywords, further reading, as well as advice on applying your ideas and links to the Australian Professional Standards for Teachers. Positive Behaviour Support has gained significant attention in Australia over the past two decades and its principles now underpin many successful systems and practices in schools, community and disability services. This book will be a foundational resource for implementers and coaches of PBS, educational leaders and policy advisors, pre- and in-service teachers, as well as researchers"--
Includes bibliographical references and index.
Keywords: Behavior modification -- Australia; Educational psychology -- Australia; School improvement programs -- Australia; School management and organization -- Australia